Assessing Country Readiness for COVID-19 Vaccines : First Insights from the Assessment Rollout - World Bank (World Bank, Washington, DC, 2021)
The global COVID-19 vaccination campaign, the largest public health initiative ever undertaken, presents challenges unprecedented in scale, speed and specificities, especially in low and middle-income countries. In November 2020, anticipating the availability of safe and effective vaccines for COVID-19, the World Bank together with WHO, UNICEF, the Global Fund, and Gavi rolled out readiness assessments in more than 100 low and middle-income countries. The key insights from the assessments to date present a high-level snapshot of country readiness to deploy COVID-19 vaccines based on initial findings from ongoing assessments in 128 countries.